Canadian cinema since the 1980s : at the heart of the world - Pike, David L. (David Lawrence), 1963- (Toronto [Ont.] : University of Toronto Press, 2012)
Making a significant advance in the study of the film industry of the period, Canadian Cinema since the 1980s is also an ideal text for students, researchers, and Canadian film enthusiasts.
""6 Cronenbergâ€?s Mutant Progeny: Genre Film-making around the Turn of the Millennium""""7 The Death of the Author? The Case of Atom Egoyan""; ""8 The Canadian Mosaic: Margins and Ethnicities""; ""9 Film-Making at the Heart of the World: Guy Maddin""; ""Conclusion""; ""Notes""; ""Works Cited""; ""Index""; ""A""; ""B""; ""C""; ""D""; ""E""; ""F""; ""G""; ""H""; ""I""; ""J""; ""K""; ""L""; ""M""; ""N""; ""O""; ""P""; ""Q""; ""R""; ""S""; ""T""; ""U""; ""V""; ""W""; ""X""; ""Y""; ""Z""
Includes bibliographical references (pages 317-336) and index.
eBooks on EBSCOhost
Keywords: Motion pictures -- Canada -- History and criticism; Motion picture producers and directors -- Canada; Cinéma -- Canada -- Histoire et critique; Producteurs et réalisateurs de cinéma -- Canada; PERFORMING ARTS -- Film & Video -- History & Criticism; PERFORMING ARTS -- Reference; Motion picture producers and directors; Motion pictures; Canada; Electronic books; Criticism, interpretation, etc